Innate lymphoid cells in bone marrow and peripheral blood of healthy individuals and in bone marrow of patients with myelodysplastic syndromes - Bento, Laiz C.; Cebinelli, Guilherme Martelossi; Bacal, Nydia Strachman; Marti, Luciana Cavalheiro (Frontiers in Immunology, 2025)
IntroductionInnate lymphoid cells (ILCs) are a recently characterized subset of lymphocytes with critical effector and regulatory functions. Based on distinct phenotypic markers and cytokine secretion profiles, ILCs are classified into three subtypes: ILC1, ILC2, and ILC3. The bone marrow (BM) microenvironment in myelodysplastic neoplasms (MDS) is characterized by heightened cytokine levels and dysregulated inflammatory responses, potentially affecting immune cell composition. In this study, we aimed to assess the frequency and absolute number of ILCs in the BM and peripheral blood (PB) of healthy individuals (HI) and compare them to those in MDS-BM.MethodsILC subsets were identified and quantified using multiparameter flow cytometry and histological analysis of BM and PB samples.ResultsILC1 populations were consistently detected in all PB and BM samples. In contrast, ILC2 and ILC3 subsets were present in both BM and PB of healthy individuals but were largely absent in MDS-BM samples. Additionally, our findings suggest the existence of a potential maturation trajectory for BM-resident ILCs.DiscussionThese data indicate a disruption in the ILC maturation continuum within the MDS-affected BM compared to healthy BM, potentially contributing to the immunopathogenesis of MDS.